2017
DOI: 10.1111/eth.12623
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of the mechanism underlying sexual segregation at communal roosts of harvestmen (Prionostemma spp.)

Abstract: Experimental test of the mechanism underlying sexual segregation at communal roosts of harvestmen ( Prionostemma spp.) Permalink https://escholarship.org/uc/item/3wn684vc Journal Ethology, 123(8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
3
0
3
Order By: Relevance
“…Also, since grouping behavior occur in certain clades, harvestmen can rely on a combination of chemical cues from feces, pheromones, substrate impregnated with conspecifics' odor, and cuticular compounds, as reported for other arthropods (cockroaches and spiders) (Machado & Macías-Ordoñez 2007). Although these stimuli may act as chemical cues in aggregations, their roles in mutual attraction remain to be experimentally tested (see Harvey et al 2017), as well as if scent-gland secretions functions as aggregation pheromones.…”
Section: Harvestmen Systematics and Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, since grouping behavior occur in certain clades, harvestmen can rely on a combination of chemical cues from feces, pheromones, substrate impregnated with conspecifics' odor, and cuticular compounds, as reported for other arthropods (cockroaches and spiders) (Machado & Macías-Ordoñez 2007). Although these stimuli may act as chemical cues in aggregations, their roles in mutual attraction remain to be experimentally tested (see Harvey et al 2017), as well as if scent-gland secretions functions as aggregation pheromones.…”
Section: Harvestmen Systematics and Biologymentioning
confidence: 99%
“…The sex ratio in aggregations of Prionostema is commonly 1:1, although some groups are either male or female skewed (Grether et al 2014b). Harvey et al (2017) experimentally demonstrated that this skew is caused by sex-specific differential recruitment through chemical signals. Together, these data suggest that sclerosomatids can form aggregations for several reasons, and females can return to the more aggregations more frequently, can be more sensitive to disturbance, or have different microhabitat preferences than males (as suggested by Grether et al 2014b).…”
Section: D Reproductive Tasksmentioning
confidence: 99%
“…atraem machos coespecíficos e uma possível explicação para essa atração está relacionada ao maior deslocamento deles (Grether et al, 2014;Harvey et al, 2017 cuspidatus podem deixar compostos pouco voláteis como hidrocarbonetos cuticulares nos abrigos, como observado em algumas baratas e joaninhas (Rivault & Cloarec, 1998;Durieux et al, 2012). Alguns estudos inclusive mostram evidências de hidrocarbonetos cuticulares sendo utilizados para o reconhecimento de abrigos (Lenoir et al, 2009;Rivault & Cloarec, 1998 (Willemart & Hebets, 2012;Fernandes & Willermart, 2014;.…”
Section: Experimento 2: Atração Por Abrigounclassified
“…Em Laniatores, até o momento não sabemos quais pistas esses animais utilizam para retornar ao abrigo, mas em outra subordem de Opiliones há evidências que pistas químicas de coespecíficos são utilizadas durante o retorno ao ambiente de repouso Harvey et al, 2017 . As fêmeas de N. maximus já foram observadas forrageando a uma distância de até 1,5 metros de distância de suas desovas .…”
Section: Introdução Geralunclassified
See 1 more Smart Citation